1998
DOI: 10.1093/jnci/90.23.1801
|View full text |Cite
|
Sign up to set email alerts
|

Variability and Accuracy in Mammographic Interpretation Using the American College of Radiology Breast Imaging Reporting and Data System

Abstract: Considerable variability in interpretation of mammographic examinations exists; this variability and the accuracy of mammography are neither improved nor diminished with use of BI-RADS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
177
2
8

Year Published

2004
2004
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 269 publications
(195 citation statements)
references
References 23 publications
8
177
2
8
Order By: Relevance
“…However, there continues to be some practice variation in the interpretation of radiologic findings. [3][4][5] Adding to the practice variability is that breast imaging and biopsy are also performed by nonradiologists (surgeons). Such variability in practice may affect the pathologist's ability to correlate pathologic and radiologic findings.…”
mentioning
confidence: 99%
“…However, there continues to be some practice variation in the interpretation of radiologic findings. [3][4][5] Adding to the practice variability is that breast imaging and biopsy are also performed by nonradiologists (surgeons). Such variability in practice may affect the pathologist's ability to correlate pathologic and radiologic findings.…”
mentioning
confidence: 99%
“…Therefore, the results closely approximate that expected in actual practice. Secondly, literature has shown that interobserver agreement for the BI-RADS assessment is only fair to moderate (Elmore et al, 1994;Beam et al, 1996;Kerlikowske et al, 1998 ;Redondo et al, 2012 ). To warrant consistent interpreting, the study was designed to exclude the factor of interobserver variation that all breast imaging were interpreted by the same experienced radiologist.…”
Section: Discussionmentioning
confidence: 99%
“…Hatta BI-RADS 5 lezyonlarda uyum en yüksek oranda bulunmuştur. Ciatto ve arkadaşlarının [4] 50 vaka ve 12 radyolog arasında yaptıkları bir çalışmada da benzer oranlar saptanmıştır Bizim çalışmamız-da kanserli olguların iki radyolog arasındaki uyumu, kanserli olmayan olgulardan daha iyiydi ancak Kerlikowske ve arkadaşla-rının [10] yaptığı benzer bir çalışmada bu uyum kanserli olmayan normal mamografili olgularda daha belirgin bulunmuştur. Bunun nedeni BI-RADS kategorileme sisteminde malignite yö-nünden şüpheli olgulara ek tetkik gerektiren olgu, yüksek olası-lıkla malign veya biyopsi gerektiren olgular şeklinde değişik yaklaşımlar yapılabilmesi ve bunun da maligniteleri kategorilemede çeşitlilik oluşturduğunu belirtmişler.…”
Section: Discussionunclassified